Restrições ao princípio da ampla defesa no processo administrativo-tribuário - Altoé, Marcelo Martins (2007)
As referencial theoric of the research the thought of Robert Alexy, searchs this present work to discussion the permanent controversy on the collision of fundamental rules, between the basic forms to pay to tributes and the basic expression to legal defense. The main objective is to show a security and rational to approach the collision between the informed right and the basic rules at to arrive at a final result that identifies which must take advantage in the analysis of the case concrete, it means of the subjection of forecasts contained in the referring legislation to the administrative proceeding tributary that the same time where it promotes the tributary rules or law, restricts the right legal defense. The necessity of valuation and perfectioning of the administrative proceeding tributary to effectively become an access way justice through the guardianship, members of the administration, the jobs intends to identify if the created restrictions to speed up proportional the administrative proceeding are. Therefore, constitutional through the solution of the collision that if bases on knowing if such ways that they foment the tributary law justify the restriction to legal defense.